Note on Degree of Convergence of Sequences of Rational Functions of Prescribed Type - Walsh, J. L. (1970)
This note studies the degree of convergence of various sequences of rational functions of given types which are of best approximation to a given function analytic on a given point set and meromorphic on a larger set. The sequences are conveniently represented by the analog of the Padé table.